GDP Growth Rate: A Comparative Study of Selected Developing Countries - Rathod, Manojkumar T. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
India has emerged as the fastest-growing economy in the world in the last few years and is likely to be one of the top five economic powers in the world over the next 10-15 years. Therefore, a study on the growth of the Indian economy is to be very important. In this research work, a comparative analysis has been done on the GDP growth rate of selected twenty developing countries. This study is based on secondary data. The last twenty years’ GDP growth rate of selected developing countries have been compared and analyzed in this study. ANOVA and paired t-tests have been used to test the research hypotheses. The major findings of the study reveal that there is a significant difference between the GDP growth rate of selected developing countries. The GDP growth rates of India, Bangladesh, Georgia, and Armenia are higher compared to other developing countries. Countries like Hungary, South Africa, Iran, and Namibia performing very poorly in these criteria. Another important conclusion of the research is that the majority of developing countries have survived from the adverse effects of COVID-19 and these economies are growing up now steadily.